Recurrent Bell's palsy in a young woman - Ngow, Harris Abdullah; Wan Mohd Nowalid, Wan Khairina; BB, Hamidon (Singapore Medical Association, 2008)
Bell's palsy is a benign lower motor neuron facial nerve disorder. It is almost always unilateral. We report a 20-year-old nulliparous woman with five episodes of recurrent Bell's palsy. A review of recent medical literature revealed a paucity of case reports involving an individual with five episodes of recurrent Bell's palsy, with none found in Asian neurology medical literature. Despite the multiple episodes of Bell's palsy recurrences, the patient did not suffer much neurological sequelae from the disease.